Changes in foot pressure distribution during a combined running and cycling exercise - Hottenrott, K.; Hoos, O.; Sommer, H.-M. (1998)
The great demand in training of long distance runners very often causes overload of the muscular-sceletal-system with typical injuries and overuse syndroms, i.e. fascitis of the plantar fascia, "skin-split"-syndrom and patellar and achilles fascitis. Alternative training methods like cycling seem to be useful to reduce overload. However, knowledge about how triathlon specific combined exercises effect running economy and foot pressure distribution is required to value this training in long distance running and cycling. The following analysis of a combined running and cycling exercise provides data on these effects and shows a relation to cross-training as described previously Conclusion: Athletes should be careful when practicing running immediately after cycling in order to reduce vertical stresses. Besides new programs of physical exercise are required to optimize muscular efficiency after cycling. (Presentation held at the ISBS-98, Konstanz, 21-25. Juli 1998)